The Influence of Motivation and Work Environment on Employee Performance Mediated by Job Satisfaction on Employees of PG Kebon Agung Malang - Mujtaba Alfan Nur; Fauzan Almanshur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study was to examine how motivation and work environment affect employee performance through job satisfaction as a mediating variable at PG Kebon Agung Malang. This study used a quantitative method with a simple random sampling technique with 110 respondents. Data collection was carried out by distributing questionnaires directly to respondents. The analysis tool used was SmartPLS 3.0. The results of this study indicate that the motivation variable (X1) does not directly affect employee performance (Y) with a value of 0.279>0.05. The work environment variable (X2) has a positive and significant effect on employee performance (Y) with a value of 0.000<0.05. The job satisfaction variable (Z) has a positive and significant effect on employee performance (Y) with a value of 0.000<0.05. The motivation variable (X1) has a positive and significant effect on job satisfaction (Z) with a value of 0.000<0.05. The work environment variable (X2) has a positive and significant effect on job satisfaction (Z) with a value of 0.000<0.05. In addition, the results of the study indicate that the motivation variable (X1) has a positive and significant effect on employee performance (Y) through the mediating role of job satisfaction (Z). The job satisfaction variable (Z) is also able to mediate the influence of the work environment (X2) on the performance of employees of PG Kebon Agung Malang.